Implementation Of History Learning Through The Example Of Buya A. R. Sutan Mansur In SMA Muhammadiyah 3 Surakarta - Ihsan Ihsan; Hermanu Joebagio; Sariyatun Sariyatun (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to examine:1.) Implementation of Historical Learning through the Exemplary of Buya A. R. Sutan Mansur in SMA Muhammadiyah 3 Surakarta. 2.) Teachers' Constraints in Implementing History Learning at SMA Muhammadiyah 3 Surakarta. This study uses a qualitative method with a Discourse Analysis approach. Data were collected through observation, in-depth interviews, and documentation study. Data analysis techniques used interactive analysis by Milles and Huberman. The results of this study indicate:(1) The implementation of historical learning through the example of Buya AR Sutan Mansur at SMA Muhammadiyah 3 Surakarta has been running quite well and effectively, during the Covid 19 Pandemic through Google Classroom, in history learning the teacher has compiled a learning tool consisting of a syllabus , RPP and the application of Buya AR Sutan Mansur's exemplary values in the history of teacher learning have brought out the exemplary values of Buya AR Sutan Mansur which consist of religious values, nationalism values, hard work values, independence values and very high steadfastness.(2.) Teachers' Constraints in Implementing History Learning at SMA Muhammadiyah 3 Surakarta, namely inadequate learning resources, and insufficient learning time, while the subject matter is large, due to the different character of students.